Comparative Analysis of Physical Facilities Management in Public and Private Secondary Schools in Ilorin West Local Government, Kwara State - Kamaldeen, Olohundare Sulyman; Abdulrafiu , Alaaya; Abdulrauf, Busirat Iyabo; Adaramaja, Sheu Muritala; Jibrin, Isah (International Journal of Educational Management, 2021)
This study examined a comparative analysis of physical facilities management in public and private secondary schools in Ilorin West Local Government, Kwara State. The study adopted a descriptive research design of survey type and the study population comprised all the teachers in public and private secondary schools in the Local Government Area. Through random sampling, 15 private secondary schools and 11 public secondary schools formed the sample. From each of the sampled schools, 15 teachers were sampled to arrive at 420 respondents. A validated and reliable instrument “Comparative Analysis of Physical Facilities Management Questionnaire” (CAPFMQ) was used for data collection. An independent t-test analysis was used to test the three hypotheses formulated for the study. The study's findings revealed that there was a significant difference between classrooms, laboratories and libraries management in public and private secondary schools in Ilorin West Local Government, Kwara State. The study concluded that classrooms, laboratories and libraries management was carried out better in private than public secondary schools. It was recommended, among other things, that proprietors and proprietresses of the private secondary schools should not relent in the management of classrooms in their schools by ensuring that they are adequately provided, utilised and maintained; while the Kwara state government should also intensify efforts in managing classrooms in her schools in the Ilorin West Local Government Area, to facilitate the actualisation of the stated goals.